A indústria do audiovisual no Brasil: uma análise a partir de dados cross-section e longitudinais - Felipe Lacerda Diniz Leroy (2013)
The empirical literature, both nationally and internationally, on "Economics of Culture" is recent and poorly consolidated. When the analysis is restricted to the creative industry and, in particular, the Brazilian audiovisual industry, subject of this thesis, there is no study that evaluates the segment in its many facets, whether as their form of organization, the composition of the market work or behavior of the supply of equipment and demand for audiovisual goods. Existing studies are limited to discussing the origin of the term creative industry and its relationship with the cultural industry, restricting the chronological facts. This thesis has as main objective to analyze the organizational form of the audiovisual industry in Brazil, considering the changes brought about by the digital age and the new technologies of information and communication technologies (ICTs), from an empirical approach. With support on data obtained restricted by the Brazilian Institute of Geography and Statistics (IBGE), seeks to evaluate possible variables that explain the net sales revenue of firms that comprise the Annual Industrial Survey and Annual Survey of Services. It is believed that this is an indirect way to identify a possible market concentration of audiovisual firms, which in turn affects the behavior of the industry as a whole. Promotes it here a study with data from the reported studies over a period of ten years. The empirical exercise is conducted based on a panel data model. Organized a panel for the firms that supply inputs for industry, PIA members and service providers, comprising the PAS. The main contribution of this work is to detect a possible concentration of audiovisual firms in certain regions of Brazil and to point the factors leading to this fact. The results show that, even tending to decrease, the regional concentration remains in the Southeast region of Brazil, with the highest prevalence in the states of São Paulo and Rio de Janeiro, the creative classes remain concentrated in the most economically developed and have amenities that attract workers to the audiovisual industry, and that variables such as "market share" and "wages paid to workers audiovisual" play a key role in explaining the net sales. This result leads to the conclusion that the mark-up practices are common in this industry and that both consumers and the fringes of this oligopolistic structure bear market imperfections. In this sense, it is believed that incentives for both phonography as for cinematography are essential to the development of the sector and increased access to goods and audiovisual services.